The Extended Pterional Approach and Microsurgery Resection for Craniopharyngiomas, Operative Nuances and Results: A Series of 29 Patients - Lynch, Jose Carlos; Pereira, Celestino; Manicacci, Valérie; Gonçalves, Mariangela; Welling, Leonardo; Lenk, Rudy (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2016)
Objective The aim of this paper is to observe if the extended pterional approach for the removal of craniopharyngiomas is safe and effective. The mortality, morbidity, and recurrence rates are presented and discussed.Method This is a retrospective analysis of 29 craniopharyngioma patients who underwent surgery between January 1988 and December 2014 at the Department of Neurosurgery of the Hospital Federal dos Servidores do Estado, Rio de Janeiro, Brazil. The charts, operative reports and imaging studies were reviewed.Results We identified 17 males (58.6%) and 12 females (41.3%) ranging in age from 0.6 to 84 years (mean 57.4 years). Thirteen (44.8%) patients were infants or adolescents. Surgical mortality occurred in one patient (3.4%). Gross total tumor removal was achieved in 15 (51.7%) patients. The median follow-up time was 7.1 years.Conclusion The extended pterional approach provides adequate access to craniopharyngiomas, and the majority of lesions could be totally removed, with a low mortality rate, but the best treatment for craniopharyngiomas remains controversial.
Keywords: extended pterional approach craniopharyngiomas; microsurgery; intracranial tumors; radical resection; tumor recurrence